Healthy Life-Style of Students: Sociological Approach - Panachev, Valery; Zelenin, Leonid; Opletin, Anatoly; Legotkin, Aleksandr; Ovchinnikov, Viktoria (International Journal of Engineering and Technology, 2018)
The ancient Greek philosopher Plato called movement as â€œsalutary part of medicineâ€, while writer and historian Plutarch â€“ as â€œstorehouse of lifeâ€. Do we always apply efforts in order this â€œstorehouseâ€ be full? Today in the age of scientific-technological progress large-scale utilization of manual labour has been practically disappeared and there has been opened the door for the so called â€œdiseases of the centuryâ€. The analysis of the results of studentsâ€™ health and healthy life-style problems study has been presented in the article. The role of physical culture and of the department of physical culture in this process has been determined. The ways of universityâ€™s educational environments resources stirring up for this problem solution have been outlined. Many people try to fully protect themselves against physical activity. They think that the less physical activity the healthier they become. Many students try to make their physical activity less thereby breaking their health. In any ways they try to obtain health certificates in order not to attend physical culture lessons and practically in all cases they get moral support of parents and what is the worst of doctors.Â Â Â